Pomegranate extract supplementation improves lung function parameters and IL-35 expression in participants with mild and moderate persistent allergic asthma: A randomized, double-blind, placebo-controlled trial - Shateri, Zainab; Hosseini, Seyed Ahmad; Abolnezhadian, Farhad; Maraghi, Elham; Haddadzadeh Shoushtari, Maryam; Zilaee, Marzie (Frontiers in Nutrition, 2022)
Existing asthma treatments are associated with side effects and limitations, which has led to an interest in alternative and complementary therapies. Given the anti-inflammatory properties of pomegranate, the present study aimed to determine the impact of pomegranate extract supplementation on lung function parameters evaluated through spirometry, high-sensitivity C-reactive protein (hs-CRP), pro-oxidant antioxidant balance, and interleukin 35) IL-35( in participants with mild and moderate allergic asthma (based on forced expiratory volume in 1 second (FEV1) and clinical symptoms). Participants with mild and moderate allergic asthma (n = 64) were randomly assigned to two groups: the intervention group, which received two pomegranate extract capsules (500 mg/day), or the control group for eight weeks. Also, the physician prescribed similar drugs to the participants in the study. Independent samples T-test and Mann–Whitney U were used to compare the quantitative outcomes between the intervention group and the comparison group. The Wilcoxon test and the paired T-test were applied for within-group comparisons. A p-value less than 0.05 was considered significant. At the end of the study, the change levels of IL-35 in the intervention group increased significantly compared to the control group. In terms of the lung function parameters, FEV1/ forced vital capacity (FVC) (FEV1/FVC) ratio enhanced significantly in the intervention group compared to the control group. Also, the pomegranate extract significantly improved forced expiratory flow 25%–75% (FEF25-75%), FEV1/FVC ratio, and FEV1 in the intervention group. No significant changes in FEV1 values were observed between the two groups at the end of the study. Also, no significant changes were seen in other indicators. It seems that pomegranate extract can improve lung function parameters and IL-35 expression in mild and moderate allergic asthma.